Stator current model for detecting rolling bearing faults in induction motors using magnetic equivalent circuits. (15th September 2019) - Han, Qinkai; Ding, Zhuang; Xu, Xueping; Wang, Tianyang; Chu, Fulei
Highlights: Stator current model for detecting bearing faults in induction motors is proposed. Non-uniform air gap length caused by defective IMRBs is numerically obtained. Iterative numerical integration method is used to solve the stator current model. Fault characteristic frequencies in stator current spectra are identified. Some fault-related frequencies are recommended for condition monitoring of IMs. Abstract: Stator current modeling for defective induction motor rolling bearings (IMRBs) based on magnetic equivalent circuits (MEC) is carried out. A dynamic model of rotor system supported by defective IMRBs is established to numerically obtain the non-uniform time-varying air gap length. MEC modeling of a induction motor (IM) is then conducted and a magnetic equivalent network is formed by connecting the flux tubes with nodes. After considering the nonlinear air gap permeance, nonlinear iron material and magnetic saturation, an iterative numerical integration method is proposed to solve the stator current model. Finite element analysis and dynamic tests on a typical IM are carried out for verification. Based on these, the fault characteristic frequencies in stator current spectra are, respectively, identified for outer race spall, inner race spall and ball spall. Fault-related frequencies are basically represented by the combinations between the passing frequency (outer race, inner race or ball), its harmonics and power supply frequency. Due to the modulation of rotor (or cage) rotation, higher harmonics of rotor frequency (or cage frequency) participate in the fault-related frequencies of the inner race (or ball) spall. Some fault-related frequencies, which might be more suitable for condition monitoring of induction motors, are recommended by comparing the slope of each spectral amplitude varying with spall width.